Developing Ayopanen Applications For Transaction Management of Agricultural Products Based on Website - Putra, Rendra Pratama; Eko Wulandari, Sri Hariani; Ningsih, Norma (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2018)
Ayopanen is an application-based marketplaces websites engaged in marketing. Application of Ayopanen used to bridge farmers who sell its products and customers that want to buy products from farmers in particular chili. Current customer complain because the price of the retail traders in Chili varies rapidly in a fairly short period of time. The purpose of this research is to make the application Ayopanen for the management of sales transaction-based website in order to make the price of products sold by farmers is not much different when it gets to the customer, because the products are sold in take and Ayopanen managed by the farmers directly and bypass the sales from the farmer to the distributor to the merchants of hunter-gatherers. Trial results show that Ayopanen applications can perform transaction product sales from farmers at a price that is cheaper than the price of a given retail merchants or distributors at this time to the customer